Prediction of Consistency of Pituitary Adenomas by Magnetic Resonance Imaging - Smith, Kyle A.; Leever, John D.; Chamoun, Roukoz B. (Journal of Neurological Surgery Part B: Skull Base, 2015)
Objective Pituitary adenomas are typically soft. The prevalence of fibrous adenomas is ∼ 5 to 13%. Firm tumors are difficult to remove by curettage or suction. Predicting fibrous adenomas by magnetic resonance (MR) imaging is typically difficult and unreliable. We propose a new prediction method based on MR T2-sequence intensity.Methods The MRIs of 36 consecutive patients with nonsecreting macroadenomas were evaluated preoperatively by a blinded radiologist. Using an MR T2-weighted sequence, regions of interest were sampled from the adenoma and cerebellar peduncle, and the ratio was calculated. Intraoperatively, tumors were graded prospectively for their consistency by the operating surgeon.Results There were 28 soft and 6 fibrous tumors. Unpaired t test for these ratios was found to be statistically significant (p < 0.0240; 95% confidence interval, −0.8229 to −0.06207). Mean values for soft tumors were found to be 1.918 (standard error of the mean [SEM] = 0.08212); firm tumors, 1.475 (SEM = 0.1179). Soft tumors were associated with ratios > 1.5 (sensitivity 100%; specificity 66.7%); firm tumors were associated with ratios < 1.8 (sensitivity 100%; specificity 42.9%).Conclusion Fibrous adenomas are typically diagnosed intraoperatively. However, their resection can be technically challenging. Using T2 intensity ratios on routine preoperative MRI allows identification of these challenging cases. The surgeon can then be better prepared for the surgical resection.
Keywords: pituitary adenomas; fibrous adenomas; adenoma consistency; endoscopic transsphenoidal; MRI